Evaluation of transform based image coders, using different transforms and techniques in the transform domain - Salvado, José (2004)
This paper addresses the most relevant aspects of lossy image coding techniques, and presents an evaluation study on this subject, using several transforms and different methods in the transform domain. We developed different transform based image coders/decoders (codecs) using different transforms, such as the discrete cosine transform, the discrete wavelet transform and the S transform. Besides JPEG Baseline, we also use other techniques and methods in the transform domain such as a DWT based JPEG-like (JPEG DWT), a JPEG DWT with visual threshold (JPEG-VT), a JPEG–like coder based on the ST, and an EZW coder. The codecs were programmed in MATLAB™, using custom and built-in functions. The structures of the codecs are presented, also as some experimental results which allow us evaluate them, and support this study.